Evaluation of genotoxicity, enzymatic alterations and cadmium accumulation in Mozambique tilapia Oreochromis mossambicus exposed to sub lethal concentrations of cadmium chloride - Akshata P. Naik; S.K. Shyama; Avelyno H. D'Costa (Environmental Chemistry and Ecotoxicology, 2020)
Cadmium (Cd), a heavy metal, is widely used in modern industries including in metal and mining industries as well as in the manufacture of NiCd batteries. Its bioaccumulation is reported to induce hazardous effects in aquatic organisms including fish. Hence, the present study was undertaken to evaluate the toxic potential of cadmium in Tilapia (Oreochromis mossambicus Peters). Fish were exposed to 3 sub-lethal concentrations of CdCl2: 7.4 μg/L (high), 3.7 μg/L (medium) and 1.85 μg/L (low) for a period of 21 days. Ten fish were used for each group and each exposure was done in triplicates. A group of 10 fish without exposure to CdCl2 was used as control. Genotoxic effects of Cd were assessed employing micronucleus assay and the comet assay. Along with these tests, alterations in the amount of the enzymes acetylcholine esterase (AChE) and catalase (CAT), as well as, the quantum of Cd accumulated in different tissues of the organism were also studied. A significant increase in DNA damage as % tail DNA and micronuclei were observed in the fish exposed to CdCl2. CdCl2 also induced a significant increase in the activity of CAT whereas a decrease in the activity of AChE was observed. A significant association was also observed between DNA damage parameters and catalase activity as well as Cd concentration in the gills. Cd may thus induce genotoxicity in O. mossambicus via oxidative stress and tissue accumulation. The combined use of these biomarkers in O. mossambicus could be used to monitor Cd contamination in the aquatic environment.